1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Assertion :If x=√cos2θ+√cos2θ√cos2θ+...∞ and y=√secθ−√secθ−√secθ−...∞ then (x2−x)(y2+y)=1 Reason: If z=√tanθ+√tanθ+√tanθ+...∞ then z2=tanθ+z.

A
Both Assertion and Reason are correct and Reason is the correct explanation for Assertion
No worries! We‘ve got your back. Try BYJU‘S free classes today!
B
Both Assertion and Reason are correct but Reason is not the correct explanation for Assertion
No worries! We‘ve got your back. Try BYJU‘S free classes today!
C
Assertion is correct but Reason is incorrect
No worries! We‘ve got your back. Try BYJU‘S free classes today!
D
Assertion is incorrect but Reason is correct
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
Open in App
Solution

## The correct option is D Assertion is incorrect but Reason is correctReason:z=√tanθ+√tanθ+√tanθ+...∞⇒z=√tanθ+z⇒z2=tanθ+z⇒z2−z=tanθAssertion:Using reason we getx=√cos2θ+√cos2θ+√cos2θ+...∞⇒x2−x=cos2θ ...(1)y=√secθ−√secθ−√secθ−...∞⇒y2+y=secθ ...(2)Therefore, from (1) and (2), we get(x2−x)(y2+y)=cos2θsecθ=cosθ

Suggest Corrections
2
Join BYJU'S Learning Program
Related Videos
Integration by Partial Fractions
MATHEMATICS
Watch in App
Join BYJU'S Learning Program